2021
DOI: 10.1111/1742-6723.13813
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing immediately after intubation in a children's emergency department is feasible and contributes to measurable improvements in patient safety

Abstract: Objective In 2013, our intubations highlighted a safety gap – only 49% achieved first‐pass success without hypoxia or hypotension. NAP4 recommended debriefing after intubation, but limited published methods existed. Primary aim is to implement a feasible process for immediate debriefing and feedback for emergency airway management. Secondary aims are to contribute to reduced frequency of adverse intubation‐related events and implement qualitative improvements in patient safety through team reflection and feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Adhering to time targets is important for acceptability. Although our median total duration (12 min 33 s) and debrief (9 min) were slightly longer than scheduled, they were similar to what our department had previously experienced 25 and published benchmarks 14 …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Adhering to time targets is important for acceptability. Although our median total duration (12 min 33 s) and debrief (9 min) were slightly longer than scheduled, they were similar to what our department had previously experienced 25 and published benchmarks 14 …”
Section: Discussionsupporting
confidence: 72%
“…16,24 Adhering to time targets is important for acceptability. Although our median total duration (12 min 33 s) and debrief (9 min) were slightly longer than scheduled, they were similar to what our department had previously experienced 25 and published benchmarks. 14 Other contributing factors included senior staff endorsement, successful time selection with flexibility (Thursday mid-morning as the most likely to have available cubicles and staff) and creating a memorable programme name (KISS).…”
Section: Iss and Translational Simulation Programme Successsupporting
confidence: 75%
“…Most papers did not quantify when immediate CD occurred; however, those that did reported that it took place minutes to hours after a specific event (see online supplemental material for details). Immediate CD lasted anywhere from 1 min to 20 min1 11 13 15 23 35–38 40–45 and was reported to be used by teams working with adult (n=15) and paediatric (n=12) populations.…”
Section: Resultsmentioning
confidence: 99%
“…Teams were reported to engage in immediate CD predominantly after traumatic or unexpected events such as resuscitation, major trauma, patient death or falls. Papers reported that all team members were invited to attend immediate CD, including non-clinical staff 11 13 21 35 45–50. This meant composition of groups engaging in CD varied considerably although medical and nursing staff were the most frequently reported 11 13 15 17 23 35 37 42 46 51 52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation